Overcoming virtual distance: a systematic review of leadership competencies for managing performance in telework - Bravo-Duarte, Felipe; Tordera, Núria; Rodríguez, Isabel (Frontiers in Organizational Psychology, 2025)
IntroductionLeadership in organizations is facing important challenges related to technological and social developments. The widespread use of teleworking and remote work requires organizations to identify and develop leadership competencies adapted to this work context. This structured literature review explores empirical evidence on theleadership competencies that facilitate telework and how they contribute to achieving high levels of performance in teleworkers.MethodsWe analyzed 22 quantitative and 15 qualitative empirical articles (2000–2024) following PRISMA guidelines. We selected only research that concentrates on specific leadership competencies.ResultsThe review shows that competencies oriented to decrease operational and social distance at work are positively related to individual and team task performance in organizations. There is some evidence of the relationship of those competencies with other dimensions of performance such as innovative performance or OCB. Leaders' digital communication emerges as the foremost competency, along with goal management, support and empowerment. To some extent, mechanisms such as trust, autonomy, and media usage have been found as intervening mechanisms. Moderators such as teleworkers' self-management and geographical distance have been identified.DiscussionSubstantial gaps in the literature were identified, including the lack of longitudinal studies, limited research on contextual/adaptive performance, and lack of attention to adapting leadership competencies to digital settings. The findings provide guidelines for leadership training and development interventions tailored to telework, considering that traditional leadership competencies may need adaptation for telework and consider specific issues in this context.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42023473498, identifier: CRD42023473498.